Impact of magnetic resonance urography and ultrasonography on diagnosis and management of hydronephrosis and megaureter in paediatric patients - Peer Wildbrett; Sönke Langner; Holger Lode; Jürgen Abel; Sylke Otto; Norbert Hosten; Winfried Barthlen (Wolters Kluwer Medknow Publications, 2012)
Background: (1) To evaluate the diagnostic value of magnetic resonance urography (MRU) in comparison with ultrasonography (US) to determine the extent of upper urinary tract dilation and (2) to evaluate the impact of MRU on therapy management. Materials and Methods: From January 2005 to December 2010, paediatric patients with hydronephrosis or megaureter who underwent MRU in addition to standard work-up imaging were included. Data were retrospectively collected and analysed in comparison with the data obtained from results by US. Results: Forty-five patients with upper urinary tract dilatation were included into the study. Twenty-six patients (58%) had a hydronephrosis and 19 patients (42%) presented with a megaureter. Diagnosis was established in all patients by multimodulary imaging work-up including micturating cysto-urethrography, MAG3 renography, US and MRU and could be confirmed in all patients who underwent surgery (n = 28). Hydronephrosis was detected in 26 of 26 patients by US (100% sensitivity) and in 25 of 26 patients (96%) by MRU (Not significant (n.s.)). Megaureter was detected in 17 of 19 patients (sensitivity 89%) by US and in 18 of 19 patients (sensitivity 95%) by MRU (n.s.). In all 45 patients, MRU had no impact on surgical or conservative management of hydronephrosis or megaureter. Conclusion: In our experience, MRU was not superior to US in detecting hydronephrosis or megaureter and had no impact on the surgical or conservative management of upper urinary tract dilation.